Low-temperature magnetism of synthetic Fe-Ti oxide assemblages - Engelmann, Ralf; Kontny, Agnes; Lattard, Dominique (Journal of geophysical research, 2010)
Low-T magnetometry (<300 K) is increasingly used to identify magnetic mineral assemblages. The present work aims at establishing a robust data basis for the characterization of polycrystalline synthetic Fe-Ti oxide assemblages from low-T magnetic measurements. The two-phase samples contained ilmenite-hematite solid solutions (ilmenitess) with compositions near to the ilmenite end-member (XIlm > 0.69), that coexisted either with titanomagnetites or with pseudobrookitess of intermediate to Ti-rich compositions (XUsp > 0.6; XFpb > 0.57). Single-phase samples of ilmenitess and titanomagnetite were also prepared and measured to underpin the results on the two-phase assemblages. We have concentrated on in-phase and out-of-phase AC susceptibility and saturation remanence and some hysteresis measurements. The temperature-dependent susceptibility and remanence curves reveal diagnostic, composition dependent signals for both ilmenitess and titanomagnetite. In particular, titanomagnetite is distinguished by frequency-dependent signals in the in-phase and out-of-phase susceptibility curves. We have focused on critical transition temperatures for ilmenitess such as Curie (TC) and Néel temperatures (TN), the spin glass transition temperature (TG) and the blocking temperature (TB). We observe a continuous decrease of TC with increasing XIlm down to about 0.93 and a slight increase of TN for XIlm between 0.95 and 1.0. TG is constant for XIlm between 0.76 and 0.95 and absent for 0.98 < XIlm < 1.0, where antiferromagnetic behavior occurs. TB is only slightly lower than TC for 0.84 < XIlm < 0.94, indicating a very restricted “superparamagnetic” field that vanishes for higher XIlm values. The new data for ilmenitess allow the construction of a revised, more physically appealing low-temperature phase diagram for this system. We observe two very good linear correlations between the peak temperature in the χ′-T curves and XIlm, one for the range 0.69-0.92 and one for 0.95-1.00, which can be useful for simple estimates of ilmenitess compositions.